High-Resolution Laser-Induced Breakdown Spectroscopy (HR-LIBS) Applied to the Analysis of Isotopically Labelled Organic Molecules - Cabalín-Robles, Luisa María; Lucena Navarro, Patricia; Forés, Laura; Vadillo-Pérez, José Miguel (My University, 2026)
Laser-induced breakdown spectroscopy (LIBS) is a versatile analytical technique that can provide elemental and molecular information in real time. It is applicable to various fields, including planetary exploration [1,2], environmental analysis and materials science. The development of high-resolution LIBS (HR-LIBS) significantly improves the ability to resolve fine spectral details, including isotopic shifts. These shifts are of particular interest in astrobiological studies aimed at identifying biosignatures on Mars. This work focuses on characterizing HR-LIBS spectra of isotopically labelled organic molecules, paying particular attention to the diatomic CN and C₂ fragments, which are potential molecular biosignatures. This study compares LIBS spectra obtained under two different environmental conditions — terrestrial air and a simulated Martian atmosphere (CO₂ at 7 mbar) — to evaluate the effect of surrounding gas composition on plasma formation and molecular emission. Samples of urea and benzamide, as well as their enriched ¹³C and ¹⁵N isotopologues, were prepared in pellet form and analyzed using an Nd:YAG laser (1064 nm) and a high-resolution Echelle spectrograph. Emission spectra were recorded in the ultraviolet–visible region, focusing on the CN violet system (Δν = 0 and +1 transitions) and the C₂ Swan bands. Isotopic shifts between the ¹²C¹⁴N–¹³C¹⁴N and ¹²C¹⁴N–¹²C¹⁵N isotopes were measured for the first time at high resolution. The results reveal that molecular emission intensities are higher in air than in CO₂, due to the availability of atmospheric nitrogen in CN formation. The observed isotopic shifts in HR-LIBS spectra are in the order of picometers, which confirms the necessity of using high-resolution instrumentation to distinguish them accurately. Furthermore, simulated spectra generated using commercial software were employed to validate the calibration and spectral resolution of the experimental setup. This study demonstrates the potential of HR-LIBS as a powerful analytical tool for isotopic and molecular analysis relevant to astrobiology and the search for life on other planets. The ability to detect and resolve isotopic molecular signatures such as CN and C₂ under Martian-like conditions reinforces the applicability of LIBS in upcoming space missions.
Keywords: Espectroscopia - Congresos; HR-LIBS; Isotope shift; High-resolution spectroscopy; CN; C₂; Biosignatures; Martian atmosphere